Evaluation the effect of acitretin on ocular surface parameters in psoriatic vulgaris patients - Shariff, Saidatulakma (2021)
Objective: To evaluate the effect of oral acitretin on ocular surface parameters which are, time of tear film to loss it integrity (by Tear Break up Time (TBUT)), production of tears by lacrimal gland (by Schirmer test), and score for Ocular Surface Disease Index (OSDI) in psoriatic vulgaris patients. Design: A prospective analysis of 29 patients with psoriasis vulgaris who need step up treatment to oral acitretin. Outcome measures included patients’ demographic data, types and duration of previous treatment for psoriasis received before, tear break-up time (TBUT), Schirmers’ test, and Ocular Surface Disease Index (OSDI) at baseline, 3 months and 6 months of treatment. Result: : No statistically significant changes were found in mean for TBUT, Schirmers test and OSDI in psoriasis vulgaris patient treated with oral acitretin for 6 months durations. Conclusion: Ocular surface integrity and tear film are not affected by 6 months therapy with oral acitretin in psoriasis vulgaris patients.